F‐wave latencies in patients with diabetes mellitus. Issue 6 (27th January 2014) - Pan, Hua; Jian, Fan; Lin, Jinxi; Chen, Na; Zhang, Chunfang; Zhang, Zaiqiang; Ding, Zeyu; Wang, Yongjun; Cui, Liying; Kimura, Jun
Abstract Introduction: To evaluate the sensitivity of electrophysiologic assessments, we compared F‐waves and motor and sensory nerve conduction studies (MNCS and SNCS) in patients with diabetes mellitus (DM). Methods: We tested median, ulnar, tibial, and fibular nerves in 132 DM patients divided into those with and without clinical evidence of polyneuropathy. Results: Of 64 asymptomatic patients, 2 (3%) had MNCS or SNCS abnormalities, both of whom had F‐wave changes, whereas 21 (33%) had only delayed F‐waves, for a combined yield of 23 (36%). The corresponding values for 68 symptomatic patients consisted of 43 (63%), 14 (21%), and 57 (84%). In both groups, F‐wave latency had a higher (P < 0.05) frequency of abnormality than MNCS in all nerves. F‐wave study also surpassed SNCS in lower limb nerves. Conclusions: F‐waves of the tibial and fibular nerves are the most sensitive measure to detect subclinical or overt diabetic polyneuropathy. Muscle Nerve49: 804–808, 2014